Сюмси. От Сибирского тракта до федеральной дороги - Шубина Татьяна Семёновна (Удмуртия, 2001)
Экземпляры: Ч/з (20160329) / Инвентарный номер: 103906 / Цена: 20.00 / Авт.знак: Ш 95 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)